Evaluación formativa y desarrollo de la habilidad escritora en el idioma inglés en un contexto universitari (2019)
The current research centered its main purpose in proposing the use of formative assessment for the development of the writing ability in English as a foreign language (EFL) in students of first level of Cursos Libres de Lenguas Extranjeras (CLE) at Universidad Del Atlántico. The work was developed from a mixed approach under an interpretive paradigm, based on a non experimental descriptive research, data collection instruments were used, such as a questionnaire of 22 items, previously validated, applied to the population made up of 106 students of the first level of the CLE and 5 teachers, together with 5 observation sheets and an open interview with 6 questions. This project allowed recognizing a moderate management of the formative assessment to enhance the writing ability of English as a foreign language according to the opinion of students and teachers, as well as weaknesses in this competence after the observation records in the classes. Thus, the proposal for a Learning and Formative Evaluation Model is generated for the development of the writing in English at the first level of C